RFID Security and Privacy 7th International Workshop, RFIDsec 2011, Amherst, MA, USA, June 26-28, 2011, Revised Selected Papers - Juels, Ari; Paar, Christof (Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-worksop proceedings of the 7th International Workshop Radio Frequency Identification: Security and Privacy Issues. RFIDSec 2011, held in Amherst, Massachusetts, USA, in June 2011. The 12 revised full papers presented were carefully reviewed and selected from 21 initial submissions for inclusion in the book. The papers focus on minimalism in cryptography, on-tag cryptography, securing RFID with physics, and protocol-level security in RFID.